PENGARUH BEBAN KERJA, LINGKUNGAN KERJA, STRESS KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT VIVA - Yuni Rahayu Putri; Fauzan Fauzan (LP2M Universitas Bina Bangsa, 2024)
As a developing country, Indonesia is entering the era of a new industrial country, it cannot be separated from the wheel of international economic activity which is full of problems from various dynamics. In the current era, the skills and abilities of human resources are required to be more competitive in order to increase work activities. within the Company. In a company, employees or existing human resources are required to provide good contributions and performance to the company where they work by providing good contributions and performance to the company so that the company can achieve the targets and vision and mission that have been set because the level of success of a company can be measured through performance given by employees to their company. This research aims to analyze and test the influence of workload, work environment, work stress, and work motivation on employee performance. The method in this research is quantitative using a survey with a questionnaire. The sampling technique used was convenience sampling technique. Data analysis used was multiple linear regression analysis using SPSS version 25. The results of this study showed that workload and work environment had a negative and insignificant influence on employee performance, while work stress and work motivation had a positive and significant influence on employee performance